Corrosion and Tribocorrosion Behaviors of Fe2TiAl–Fe2Ti Alloy - Li Rui (Russian Journal of Physical Chemistry A, 2024)
In this paper, Fe 2 TiAl–Fe 2 Ti alloy was prepared by arc melting method, and its corrosion and tribocorrosion behaviors were investigated in detail. The results showed that Fe 2 TiAl–Fe 2 Ti alloy exhibited better corrosion and tribocorrosion resistance compared to 0Cr18Ni9 stainless steel in 0.5 mol/L H 2 SO 4 solution due to the formation of TiO 2 –Al 2 O 3 –Fe 2 O 3 protective layer on the surface. Compared to static corrosion, the alloy exhibits a lower corrosion potential, higher corrosion current, and noticeable fluctuations in the polarization curves under sliding conditions. With the onset of sliding, the OCP value of the alloy decreases and the current density increases, with an inversely varying relationship between the friction coefficient and the OCP, indicating a significant wear-accelerated corrosion effect. At higher potentials, the wear volume of Fe 2 TiAl–Fe 2 Ti alloy and 0Cr18Ni9 stainless steel increases, indicating that corrosion accelerates wear.